Effects of E-CRM and green operational practices on operational performance of hospitals: a case study of ASEAN countries - Mahrinasari, M.S.; Haseeb, Muhammad; Bangsawan, Satria; Sabri, Mohamad Fazli (Regional Association for Security and crisis management, 2024)
The primary aim of this research was to assess the impact of operational practices and electronic customer relationship management (E-CRM) on the operational performance of hospitals within ASEAN countries, mediated by patient satisfaction. Additionally, the study examined the moderating effects of operational green behaviour and operational management reasons. Data were gathered via a convenient sampling technique from 600 female healthcare patients across three ASEAN nations: Indonesia, Malaysia, and Singapore. Employing a quantitative deductive approach, the research utilized a cross-sectional design. The Partial Least Squares Structural Equation Modelling (PLS-SEM) technique revealed that operational practices and E-CRM significantly and positively influenced patient satisfaction. Moreover, patient satisfaction was found to positively and significantly affect operational performance. The results also indicated that operational management reasons and operational green behaviour exerted positive and significant moderating effects on the relationships between operational practices, E-CRM, and patient satisfaction. These findings contribute to theoretical advancements by providing insights for future research in novel contexts. Furthermore, they offer practical implications, emphasizing the importance of operational management reasons and green social behaviour in enhancing operational performance within companies.